Artificial Intelligence (AI) for climate action: bridging Kenya's digital divide for a greener future - Kibaara, David; Orto, Abkul; Njuguna, Patrick (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
This paper explores the dual role of Artificial Intelligence (AI) in addressing climate action and bridging the digital divide in Kenya, under the theme "Science in the Service of Climate Action." The study examines the current state of digital access and infrastructure in Kenya, identifying key socioeconomic barriers to digital inclusion. It further investigates how AI-driven solutions can mitigate climate change impacts, with a focus on applications in climate monitoring, agriculture, and renewable energy. Through a combination of case studies and policy analysis, this paper highlights successful AI initiatives that promote both environmental sustainability and digital equity. Key findings suggest that integrating AI with efforts to enhance digital access can significantly amplify climate action outcomes, fostering community resilience and environmental health. The paper concludes with policy recommendations to support the implementation of AI technologies for climate and digital inclusion, emphasizing the need for coordinated efforts by government, private sector, and civil society. This research underscores the potential of AI to transform Kenya's approach to climate challenges while ensuring equitable digital opportunities for all.